De schaatssprint: een kwestie van goed starten - Bakker, C.; Aaftink, C.; Koning, J. de (Geneeskunde & Sport, 1990)
This paper describes the sprint in speedskating. A 3D analysis of kinetics and kinematics was made on the basis of filmdata of 500 meter speedskaters, obtained at the 500 meters speedskating during the Olympic Games in Calgary (1988). Attention is paid to the technical aspects of speed skating as well as to some technical and physiological differences between male and female speedskaters. The start technique in speedskating which shows many similarities to the sprint start in athletics, is characterised by a push-off in backward direction combined with a powerful plantar flexion. Achieving higher speeds requires a change from the start to the gliding technique: a sideward push-off without flexion of the ankle. It is shown that high accelerations during the start result in fast final times. These high accelerations can be achieved by delivering high power outputs in the very first strokes. This strategy results in faster final times than the strategy of building up speed more slowly while reaching a higher final value. Verf.-Referat (Dokument übernommen aus Datenbank SPOLIT)